How Patients and Providers Weigh the Risks and Benefits of Long-Term Opioid Therapy for Cancer Pain. Issue 7 (July 2021) - Giannitrapani, Karleen F.; Fereydooni, Soraya; Silveira, Maria J.; Azarfar, Azin; Glassman, Peter A.; Midboe, Amanda; Zenoni, Maria; Becker, William C.; Lorenz, Karl A.
Abstract : PURPOSE: To understand how patients and providers weigh the risks and benefits of long-term opioid therapy (LTOT) for cancer pain. METHODS: Researchers used VA approved audio-recording devices to record interviews. ATLAS t.i., a qualitative analysis software, was used for analysis of transcribed interview data. Participants included 20 Veteran patients and 20 interdisciplinary providers from primary care– and oncology-based practice settings. We conducted semistructured interviews and analyzed transcripts used thematic qualitative methods. Interviews explored factors that affect decision making about appropriateness of LTOT for cancer related pain. We saturated themes for providers and patients separately. RESULTS: Factors affecting patient decision-making included influence from various information sources, persuasion from trusted providers, and sometimes deferral of the decision to their provider. Relative prioritization of pain management as the focal patient concern varied with some patients describing comparatively more fear of chemotherapy than opioid analgesics, comparatively more knowledge of opioids in relation to other drugs;patients expressed a preference to spend the limited time they have with their oncologist discussing cancer treatment rather than opioid use. Factors affecting provider decision making included prognosis, patient goals, patient characteristics, and provider experience and biases. Providers differed in how they weigh the relative importance of alleviating pain or avoiding opioids in the face of treating patients with cancer and histories of substance abuse. CONCLUSION: Divergent perspectives on factors need to be considered when weighing risks and benefits. Policies and interventions should be designed to reduce variation in practice to promote equal access to adequate pain management. Improved shared decision-making initiatives will take advantage of patient decision-making factors and priorities.